2016
DOI: 10.1159/000444186
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Treatment by Erlotinib and Toxic Cardiomyopathy: A Case Report

Abstract: Erlotinib maintenance treatment improves progression-free survival compared with observation after first-line chemotherapy in unselected advanced non-small cell lung cancer (NSCLC). Very few cardiac adverse effects have been observed in phase III studies on tyrosine kinase inhibitors (TKI). We report the case of a 71-year-old woman with metastatic NSCLC treated with cisplatin/pemetrexed and then erlotinib maintenance therapy. After 26 months of TKI therapy, she developed dilated cardiomyopathy. Despite symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In support of our model, recent studies reported that erlotinib induced QTc interval in patients and CV damage in rat model . In addition, an increasing number of clinical case reports of acute myocardial infarction following treatment by erlotinib in cancer patients also were reported. Gefitinib, a multitargeted tyrosine kinase inhibitor, was approved for treating lung cancer. Our combined classifiers predicted that gefitinib induced all five CV complications (hypertension, heart block, arrhythmia, cardiac failure and myocardial infarction), consistent with recent clinical and preclinical studies. , Sunitinib, a FDA-approved tyrosine kinase inhibitor for treatment of renal cell carcinoma and imatinib-resistant gastrointestinal stromal tumor in 2006, was predicted to induce all five CV complications by the combined classifiers.…”
Section: Resultssupporting
confidence: 77%
“…In support of our model, recent studies reported that erlotinib induced QTc interval in patients and CV damage in rat model . In addition, an increasing number of clinical case reports of acute myocardial infarction following treatment by erlotinib in cancer patients also were reported. Gefitinib, a multitargeted tyrosine kinase inhibitor, was approved for treating lung cancer. Our combined classifiers predicted that gefitinib induced all five CV complications (hypertension, heart block, arrhythmia, cardiac failure and myocardial infarction), consistent with recent clinical and preclinical studies. , Sunitinib, a FDA-approved tyrosine kinase inhibitor for treatment of renal cell carcinoma and imatinib-resistant gastrointestinal stromal tumor in 2006, was predicted to induce all five CV complications by the combined classifiers.…”
Section: Resultssupporting
confidence: 77%
“…Nedaplatin-induced cardiotoxicity is also rare, although it has been presented that three patients treated with nedaplatin develop chemotherapy-induced serious arrhythmias [ 11 ]. In addition, few cardiac adverse effects have been observed on tyrosine kinase inhibitors (TKIs), although long-term erlotinib maintenance may have transformed minimal cardiotoxicity into dilated cardiomyopathy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only 4 cases of cardiovascular adverse events (3 myocardial infarctions and one dilated cardiomyopathy) have been reported as side effects of erlotinib. [4][5][6] Kus, et al 4) reported two cases of ST-segment elevation myocardial infarction during erlotinib treatment for NSCLC. Ding, et al 5) also reported a similar case of myocardial infarction following erlotinib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ding, et al 5) also reported a similar case of myocardial infarction following erlotinib treatment. Pinquié, et al 6) reported dilated cardiomyopathy in a patient with NSCLC who was administered maintenance erlotinib for 26 months after 6 courses of cisplatin/pemetrexed treatment. Our case presented with heart failure without coronary artery lesions and was similar to the last mentioned case of dilated cardiomyopathy rather than the 3 cases of myocardial infarction mentioned above.…”
Section: Discussionmentioning
confidence: 99%